Peningkatan Kecerdasan Anak Melalui Pemberian ASI dalam al-Qurâan - Hanafi, Yusuf (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2012)
Todays health researchs prove that the breast milk contains a lot of content that is not found in milk formula, especially immunologic substances. Breast milk contains anti-infective agents that are clean and free of contamination. Immune substances that exist in immunoglobulins, secretory, and lactoferrin as well as the presence of factors that can stimulate Lactobacillus bifidus to protect babyâs digestive tract. Lately also known that breast milk can increase childrenâs intelligence. It could be due to nutritional milk, methods, or durations of breastfeeding. Research shows that a Taurine, Decosahexanoic acid (DHA) and Arachidonic acid (AA) exist in breast milk is very useful in the formation of the babyâs brain cells and accelerate the stimulus from the receptor organ to the brain, so that the response can be given in a fast time. Yet long before the WHO, researchers and human rights activists has been intensifying exclusive breastfeeding, the Koran was first called to breastfeed hawlayn kÃ¢milayn two full years. The Relevances between the activity of breastfeeding for two full years and the brain development of baby will be discussed in this paper.